NeuroEPO influence on the fetal heart in a placental insufficiency model of rats - Nìnive Nùñez Lòpez; Julito Dos Santos Dos Santos; Aida María Suàrez Aguiar; María Antonia Cruz García; Claudia Joffre Frías; Carmen Inés Morales Paneque; Laura López Marín (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2024)
Foundation: placental insufficiency is the most common cause of intrauterine growth retardation, which can cause cardiovascular alterations. Recently, erythropoietin therapies have been developed that protect hypoxic cardiac tissues. Objective: To evaluate the influence of human recombinant erythropoietin with low sialic acid content (NeuroEPO) on the fetal heart in a rat model of placental insufficiency. Methods: 14 Wistar rats gestated with unilateral ligation of the right uterine artery on day 16 of gestation were used. That same day, seven rats were administered NeuroEPO (0.5 mg/kg/day subcutaneously for three days) and the rest received placebo. On day 20 of gestation, the fetuses were divided into four groups: a control group, a group with intrauterine growth retardation, a NeuroEPO control group, and a group with intrauterine growth retardation and NeuroEPO. In the fetuses, placental weight, fetal weight and placental efficiency were obtained. In the histological study, the number of cardiomyocytes, number of blood vessels and quantity of collagen fibers were quantified. Results: the group with intrauterine growth retardation presented a decrease in fetal weight, the number of cardiomyocytes, the number of blood vessels and an increase in the amount of collagen fibers (p<0.05). When fetuses with intrauterine growth retardation were treated with NeuroEPO, fetal weight increased, although the weight was not similar to the control. The rest of the variables behaved similar to the control. Conclusions: the administration of this molecule improved fetal weight and allowed an adequate balance in the development of the fetal heart, perhaps due to the cytoprotective effects of this molecule.